Changes over time in multidimensional poverty: methodology and results for 34 countries - Alkire, S; Roche, J; Vaz, A (Oxford Poverty & Human Development Initiative, 2015)
This paper sets out a systemic account of changes over time in multidimensional poverty using the Alkire-Foster Adjusted Headcount Ratio and its consistent sub-indices. The techniques were then applied to the analysis of changes in the global Multidimensional Poverty Index (MPI) and related destitution measure. The analysis focused on 34 countries and 338 subnational regions, covering 2.5 billion people, for which there is a recent MPI estimation and comparable Demographic and Health Survey (DHS) dataset for analysis across time. First, it assesses overall changes in poverty and its incidence and intensity. Next, it examines changes in the MPI and its consistent sub-indices across urban-rural regions, subnational regions, and ethnic groups. Finally, the paper analyses the changes for a strict subset of the poor, who are identified as ‘destitute’ using a more extreme deprivation cutoff vector, and studies relative rates of reduction of destitution and poverty by country and region.